2020
DOI: 10.1007/s42452-020-03490-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pure rapeseed oil as a renewable fuel for agricultural machinery based on emission characteristics and long-term operation behaviour of a fleet of 18 tractors

Abstract: The usage of locally produced pure rapeseed oil fuel (R100) according to fuel standard DIN 51605 in agricultural machinery can contribute to protecting the climate, water, and soil. Besides economic aspects, uncertainties concerning the long-term operation reliability and limited exhaust emissions of R100-operated agricultural machinery are hindering market entry. Thus, the aim of this research is to evaluate field experiences, such as downtimes and repairs, engine oil quality, and cold start behaviour, over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The investigators [77][78][79][80][81][82][83][84][85][86] noticed elevated EGT with different loading conditions and operational hours. All investigator [77][78][79][80][81][82][83][84][85][86] analyzed the affecting variables and after-effects of SVOs on lubricating oil during the long-term test of 250 to 50000 cumulative hours (refer Table 7). Almutairi et al 80 performed 300 hours of durability tests on a 1C, DE to study the effects of preheated crude Jatropha oil (90°C) as engine fuel.…”
Section: Impact Of Svos On Performance and Emission Parameters Of Com...mentioning
confidence: 95%
See 2 more Smart Citations
“…The investigators [77][78][79][80][81][82][83][84][85][86] noticed elevated EGT with different loading conditions and operational hours. All investigator [77][78][79][80][81][82][83][84][85][86] analyzed the affecting variables and after-effects of SVOs on lubricating oil during the long-term test of 250 to 50000 cumulative hours (refer Table 7). Almutairi et al 80 performed 300 hours of durability tests on a 1C, DE to study the effects of preheated crude Jatropha oil (90°C) as engine fuel.…”
Section: Impact Of Svos On Performance and Emission Parameters Of Com...mentioning
confidence: 95%
“…In the same context, Sahu et al 76 reviewed the engine's output adopting a variable compression ratio DI DE engine using SVO for shortrun operations. However, some researchers [77][78][79][80][81][82][83][84][85][86] performed their investigation for short-run and long-run operation hours using SVOs. Acharya et al 87 also found that KO (PH) produces higher CO, HC lower CO2 at low load, and lower NOx at all loading conditions.…”
Section: Effect Of Svos On Engine Performance and Emission At Varying...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ettl et al [8] evaluated rapeseed oil (R100) as a renewable fuel for agricultural machinery based on long-term operation behavior and emissions of a fleet of tractors over more than 50,000 operation hours under Bavarian farm conditions. The tractors demonstrated their full functionality, and no serious engine failures were observed, while minor malfunctions and repairs occurred just occasionally.…”
Section: Introductionmentioning
confidence: 99%
“…Pure rapeseed oil as fuel for CI engines was tested and gave some positive results, especially in agriculture. The tests showed that modified tractor engines reliable operation fueled with it is possible and provide some benefits [12,13]. Rapeseed oil is approximately a C57 compound with one mole having an atomic mass of 890 [14].…”
Section: Introductionmentioning
confidence: 99%